Constitution, Law, and Morals: A Philosophical Study - Yunus, Nur Rohim (ADALAH, 2023)
The essay entitled Constitution, Law, and Morals: A Philosophical Study discusses the complex relationship between constitution, law, and morals in the theory and practice of the state. The constitution, as the highest law of a country, should ideally not only regulate legal norms formally, but should also reflect the moral values that develop in society. However, there are often clashes between applicable laws and public morality, which give rise to various legal and ethical dilemmas. Through a legal philosophy approach, this essay explores several main perspectives, such as deontology, utilitarianism, and social contract theory, in understanding how law and morals interact in the constitution. In addition, sociological studies of the thoughts of Emile Durkheim and Max Weber are also used to show how law reflects social solidarity and society's moral legitimacy. This essay highlights various cases where the law conflicts with public moral values, such as the debate over the legality of same-sex marriage, the death penalty, and freedom of expression. As a solution, a balance is needed between legality and moral legitimacy in the formation and implementation of law. With the principle of the rule of law based on morality, constitutional flexibility to social change, and legal education that integrates ethics, this essay emphasises that an ideal legal system must be oriented towards substantive justice and social welfare.